PERKERASAN JALAN (AC-WC) DENGAN BAHAN TAMBAH CAMPURAN ARANG KAYU DAN PASIR LAUT - Gery Rizki Bijaksana; Dwi Prasetyo; Juny Andry Sulistyo (UNISSULA Semarang, 2025)
This study investigates the effects of incorporating wood charcoal and sea sand as additive materials in the Asphalt Concrete Wearing Course (AC-WC) mixture. Wood charcoal, known for its porous structure and lightweight properties, is expected to enhance the absorption and bonding of asphalt binder, while sea sand is examined as a partial substitute for fine aggregates to promote the use of local materials. The experimental design includes the addition of 0%, 2%, 4%, and 6% wood charcoal by total aggregate weight, and 0%, 2%, 4% and 6% sea sand as a mixing compliment. Marshall tests were conducted to evaluate key parameters such as stability, flow, Marshall Quotient, Voids in Mix (VIM), Voids in Mineral Aggregate (VMA), and Voids Filled with Bitumen (VFB). The results indicate that the addition of 0% up to 2% wood charcoal meets the requirements of the Indonesian Directorate General of Highways (Bina Marga, 2018). These additives demonstrated improved stability and deformation resistance, though excessive usage led to decreased cohesion and moisture resistance. Overall, wood charcoal and sea sand show potential as sustainable alternative additives in AC-WC mixtures when used in optimal proportions.